β-Amyloid oligomers in aging and Alzheimer’s disease - Zahs, Kathleen R.; Ashe, Karen H. (Frontiers in Aging Neuroscience, 2013)
Alzheimer’s disease (AD) is a fatal neurodegenerative disorder, and the most common cause of dementia in the elderly. The cause of AD is not known, but genetic evidence strongly supports the hypothesis that pathological aggregation of the β-amyloid protein (Aβ) triggers the disease process. AD has a long preclinical phase, lasting a decade or more. It is during this preclinical phase, before the irreversible neuron loss that characterizes the dementia phase of the disease, that therapies are most likely to be effective. If we are to block AD during the preclinical phase, we must identify the Aβ species that are present before there are overt symptoms and that are associated with downstream markers of pathology. A specific soluble Aβ assembly, the putative dodecamer “Aβ*56,” is present in the brains and cerebrospinal fluid of cognitively intact individuals and correlates with markers of synaptic dysfunction and neuronal injury. This assembly also correlates with memory dysfunction in multiple lines of transgenic mice that model the preclinical phase of AD. We suggest that Aβ*56 has a critical role during the earliest phase of AD and might serve as a molecular trigger of the disease.